2022
DOI: 10.3389/fimmu.2021.826067
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Prebiotic Berberine Combined With Methimazole Improved the Therapeutic Effect of Graves’ Disease Patients Through Regulating the Intestinal Microbiome

Abstract: Graves’ disease, a typical metabolism disorder, causes diffuse goiter accompanied by ocular abnormalities and ocular dysfunction. Although methimazole (MI) is a commonly used drug for the treatment of GD, the efficacy of methimazole is only limited to the control of clinical indicators, and the side effects of MI should be seriously considered. Here, we designed a 6-month clinical trial that divided the patients into two groups: a methimazole group (n=8) and a methimazole combined with potential prebiotic berb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…achieves a better effect on GD than methimazole alone, and the changes in the gut microbiome include changes in levels of Lactococcus lactis, Enterobacter hormaechei, and Chryseobacterium indologenes (45). The results obtained from patients with GD reveal that changes in the gut microbiome accompany GD, which agrees with our results (45).…”
Section: A B D E F G I H Csupporting
confidence: 89%
“…achieves a better effect on GD than methimazole alone, and the changes in the gut microbiome include changes in levels of Lactococcus lactis, Enterobacter hormaechei, and Chryseobacterium indologenes (45). The results obtained from patients with GD reveal that changes in the gut microbiome accompany GD, which agrees with our results (45).…”
Section: A B D E F G I H Csupporting
confidence: 89%
“…(3) Integrative Chinese and western medicine study: GQD can enhance PD-1 blockade in CRC by remodeling GM ( Lv et al., 2019 ). Berberine has potential benefits in combination with methimazole in modulating GM composition in the treatment of Graves’ disease ( Han et al., 2021 ). In addition, complementary and alternative medicine prevention and treatment strategies such as TCM may help reduce antibiotic use ( Baars et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the level of SCFAs in the stool was also noted [129]. The prebiotic effect of berberine has been demonstrated in numerous studies [130][131][132][133]. A previous study performed on obese mice have shown that berberine is more effective in modifying the structure of the microbiome than curcumin [131].…”
Section: Herbs and Spicesmentioning
confidence: 82%